The importance of toxicity tests for development and phytotherapy registration (Research, Society and Development, 2021)
Non-clinical toxicological studies work as a foundation in the process of developing new drugs, as they anticipate risks and, therefore, reduce the probability of a new drug interfering with cellular metabolism, harming the health of the individual, in addition to not fulfilling its pharmacological function in the body. Thus, considering the therapeutic potential of medicinal plants, this paper aims to describe the importance of toxicological tests and current aspects concerning the registration of herbal medicines in Brazil. In order to carry out this work, scientific databases were searched, such as: Periódicos CAPES and Scielo, and the database was complemented with articles from Brazilian legislation. There was no search restriction regarding the language and year of publication of the scientific materials, but rather regarding the relevance of their content for this article. Thus, it was observed that the regulatory role of ANVISA is essential to prevent ineffective, toxic and poor quality drugs from reaching the market and causing problems such as intoxication, interactions with other drugs, therapeutic damage, or even death. Thus, as it is a traditional health practice and has already been revealed in several studies as being of therapeutic utility by a significant portion of the population, it is interesting to discuss the current situation of herbal medicines and the seriousness that should be taken in their development, especially in light of the trials non-clinical toxicologicals as they can prevent public health problems in the short and long term.